Phytoplankton Composition and Abundance as an Indicator of Water Quality in The Post-Sand Mining Swamp of Kranjingan, Jember - Purwandari, Anggraini Ratih (Journal of Biological Science and Education, 2024)
AbstractThe analysis of water quality in the post-sand mining swamp of Kranjingan indicates that the aquatic environment is in relatively good condition, with a neutral to slightly alkaline pH, stable temperature, and total dissolved solids (TDS) within acceptable limits. Although slight variations were observed between stations, particularly at Station 4, which recorded the highest TDS value, the overall water conditions still support the sustainability of the aquatic ecosystem and allow for various sustainable utilizations. The study's objective is to analyze the water quality in the post-sand mining swamp of Kranjingan and evaluate the sustainability of the aquatic ecosystem in the area. This research also aims to understand the composition and abundance of phytoplankton to determine the trophic status of the ecosystem. The study results show that the composition and abundance of phytoplankton in the post-mining swamp exhibit oligotrophic characteristics, with a dominance of the Cyanophyta phylum, particularly Microcystis. The highest phytoplankton diversity was found at Station 2, while Station 4 demonstrated relatively stable abundance. These findings provide essential insights into the management and utilization of post-sand mining swamps for both ecological and economic purposes. Keywords: phytoplankton, water quality, post-sand mining swamp, Kranjingan, Jember